Recent American Novelists - American Writers 22 : University of Minnesota Pamphlets on American Writers - Ludwig, Jack, 1922-2018 (Book collections on Project MUSE., 1962)
Recent American Novelists - American Writers 22 was first published in 1962. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.